Development of flower galls in Prosopis cineraria trees of Rajasthan (The Journal of Plant Protection Sciences, 2024)
Plant galls are abnormal growths caused by  stimulation of plant cells with the interaction  by the nematodes, fungus, bacteria, mites, in sect etc. (2, 24, 26). Galls can be formed in  the lamina and petioles of leaves, twigs, buds,  flowers or on the roots. Each type of gall producer is specific to a particular kind of  plant. The gall is a unique example of a plant pest relationship causing harmful effects such  as hypertrophies and tumorous (neoplasmic)  outgrowths as well as beneficial effect to the  plants in fixing nitrogen by bacteria, actino mycetes and blue-green algae. Damage by the  plant galls is not only the aesthetic problem  but also cause serious problems to the many  host plants including Prosopis cineraria, P.  glandulosa var. torreyana and P. velutina (7,  8, 11, 12, 17). In P. cineraria, four distinct  types of galls have been reported by various  workers (12, 13, 21). Galls damage the stem  branches, rachis, leaflets and flowers portions  of the Prosopis tree.
Keywords: cineraria; nematodes; abnormal